ELISA IMMUNO ASSAY IN DISEASE DIAGNOSIS - Daminov Feruz Asadullaevich; Isomadinova Lola Kamoliddinovna; Rashidov Abdurauf (TADQIQOTLAR.UZ, 2024)
Annotation. The article shows the capabilities of a modern serological research method  -  enzyme  immunoassay  in  the  diagnosis  of  infectious,  endocrine  and oncological  diseases.  Practical  examples  of  diagnosing  individual  pathological conditions, factors influencing the result, and the diagnostic value of the markers used are considered.